Municipal Waste Management Dissemination to Rural Society: A Preliminary Action Research - Astuti, Septin Puji; Setiawan, Eko; Ariana, Ariana; Nurhayati, Ervin; Rahman, Dian Arif; Saputro, Erwin Adi (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
The increasing waste due to increasing population and consumption in rural area led municipal wastemanagement in rural area essential. However, most of rural area did not have well developed municipal wastemanagement for some reasons. This community service intended to provide a contribution to society to manage municipalwaste in rural area. Action research is implemented in this community service. Focus Group Discussion (FGD) wasapplied to identify what are the main problems and decided what actions will be conducted during community service.From the first FGD, we concluded that the activities should be prepared were providing information related to negativeimpact of disposing municipal waste illegally, understanding on the type of municipal waste and how to separate them aswell as training to manage municipal waste in simple way through Takakura method. Those activities, then, conductedthrough a workshop on municipal waste management in household level